HETERORHABDITIS TAYSEARAE AND HETERORHABDITIS BACTERIOPHORA: PROMISING INDIGENOUS ENTOMOPATHOGENIC NEMATODES AGAINST VEGETABLE INSECT PEST - Pascual, Maria Lima D.; Pascual, Pet Roey L.; Alburo, Hemres M. (Journal of Agriculture and Technology Management; Journal of Agriculture and Technology Management (JATM) Volume 20 Issue 2, July-December 2017, 2018)
Commercial application of EPNs against insect pest has been successfully applied in countries like USA, Australia and Europe (Arthurs et al., 2004; Shapiro-Ilan et al., 2012). In biological control programs, however, using indigenous control agents is often preferable than using exotic ones. Therefore, a study on the identification of promising indigenous EPNs as control to common insect pests attacking vegetables is deemed necessary. Seventeen EPN isolates were collected reflecting the different soil samples taken from vegetable farms across eight municipalities in the province of Cebu. Standard filter paper bioassay (Woodring and Kaya, 1988) was followed to compare its effectivity at 0, 10, 25, 50, 100 and 200 IJs/larva in 0.5 ml of distilled against larvae of cutworm ( Spodopteralitura ), cabbage head moth ( Crocidolomiapavonana ) and diamond back moth ( Plutellaxylostella). All isolates caused mortality to diamond back moth, cabbage head moth and cutworm. However, percent mortality differed among EPN isolates/species, concentrations and insect pest. H. taysearae at 200 IJs/larva caused the highest mortality rate (64.76%) on diamond back moth larvae. Against cabbage head moth, generally the higher the concentrations the better effect. Furthermore, H. Taysearae, H. marelatus and H. bacteriophora were identified as the best isolates. On cutworm larvae, concentrations of 50 to 200 IJs/larva were most effective . . Moreover, H. bacteriophora together with H. Taysearae and H. marelatus was the most effective isolates. The pupal stage of the insect life cycle seemed less susceptible to infection while its adult stage is more susceptible to EPN infection. Both of these stages (papae and adult) undernormal conditions are spend away from the ground. From the different isolates considered, both H. taysearae and H. bacteriophora have the greatest potential for field trials considering there availability as compared to H. marelatus .